First Report of Coexistence of Three Different MDR Plasmids, and That of Occurrence of IMP-Encoding Plasmid in Leclercia adecarboxylata - Yin, Zhe; Hu, Lingfei; Cheng, Qiaoxiang; Jiang, Xiaoyuan; Xu, Yanan; Yang, Wenhui; Yang, Huiying; Zhao, Yuee; Gao, Bo; Wang, Jinglin; Dai, Erhei; Zhou, Dongsheng (Frontiers in Microbiology, 2019)
Three different MDR plasmids p16005813A, p16005813B and p16005813C, which carried a total of 18 non-redundant resistance genes or gene loci, were identified in a single clinical isolate of Leclercia adecarboxylata. The p16005813A backbone showed very low levels of identity to all DNA sequences available in public databases and carried a repA gene that could not assigned into any of known incompatibility groups. The IncFII-family p16005813B and pECAZ161_KPC had essentially identical backbones. p16005813C belonged to an IncR single-replicon plasmid. p16005813A, p16005813B and p16005813C harbored three different novel MDR regions as their sole accessory modules. The MDR region of p16005813B manifested as Tn6505, which was generated from insertion of blaIMP-8-carrying In655 instead of In4 into the Tn1696 backbone. Other key antibiotic resistance elements included Tn2, IS26-mph(A)-mrx-mphR(A)-IS6100 unit, chrA region, In27, and aacC2-tmrB region in the MDR region of p16005813A, and ∆Tn9 carrying catA1, In609, and IS26-tetA(C)-tetR(C)-IS26 unit in the MDR region of p16005813C. This was the first report of coexistence of three different MDR plasmids, and that of occurrence of IMP-encoding plasmid and blaIMP-8 gene in L. adecarboxylata.